Efeito agudo de diferentes configurações de exercício de força no desempenho funcional e risco de queda em idosas destreinadas: um estudo cruzado e aleatorizado - Leandro, Leonardo da Silva (2020)
Introduction: the practice of strength training is beneficial to improve long-term balance, but little is known about the acute effects of strength training on the functional performance of the elderly. Objective: to compare the acute effect of strength exercise with different configurations on functional performance and risk of falls for untrained elderly women. Materials and Methods: this is a randomized, crossover clinical trial. Physically active elderly (n = 5) (64.2 ± 1.5 years), made 14 visits: 1th to 4th visits - familiarization; 5th and 6th visits test and retest (risk of falling [RQ], functional performance [DF], vertical jump [SV] and load test of 15 maximum repetitions [15RMs]); 7th to 14th visits - 4 experimental conditions and 4 evaluation sessions (RQ, SV and DF) after 24 hours. The squat exercise was chosen for the experimental conditions (7-day wash-out between sessions): 5x12[15RMs] repetitions with maximum intentional speed (MIS5x12); 10x6[15RMs] repetitions (MIS10x6); 5x12[15RMs] repetitions with self-selected speed (SSS5x12); 10x6[15RMs] repetitions (SSS10x6). To compare the variables of neuromuscular performance (RQ, DF, SV), lactate and perception of recovery (PSR), the two-way ANOVA with repeated measures (conditions x moments) with Bonferroni's post hoc was used; and one-way ANOVA of repeated measures to analyze the internal load between experimental conditions. Results: there was no significant difference in any of the conditions in the RF (P> 0.05); there was a very large ES of worsening of the FP immediately after the experimental condition VAS10x6 vs. MVI10x6 (P= 0.009; d= 3.40) and remained until Post-24h compared to the condition MVI5x12 (P= 0.006; d= −3.99) and MVI10x6 (P= 0.023; d= −2.81); in the VJ there was a significant global ES at the time (P< 0.05; ɳ2p= 0.68), however, there was no “condition x moment” interaction; the conditions VAS5x12 and MVI5x12 presented significant ES almost perfect in the lactate levels between the moments Post vs. Pre (P= 0.007; d= 6.34; P= 0.030; d= 4.4, respectively), there was also an increase in lactate levels at the time Post between the conditions VAS5x12 vs. MVI10x6 (P= 0.050; d= 2.04), MVI5x12 vs. VAS10x6 (P= 0.022; d= 3.20) and MVI5x12 vs. MVI10x6 (P= 0.014; d= 3.88); there was no significant difference in the perception of recovery between moments and conditions (P> 0.05), however, there was a significant increase in the internal load of the session in the comparison VAS5x12 vs. MVI10x6 (P= 0.007; d= 4.68). Conclusion: The exercise of strength with MVI and different repetitions of reserve, resulted in similar responses in the RQ in comparison to the execution with VAS and different repetitions of reserve. However, MVI10x6 seems to have less adverse effect on DF, SV, lactate and on the internal load of the session up to 24 hours post-exercise.